Role of IL6 –174C/G gene polymorphism in development of chronic HCV infection - N. A. Semyonova; N. V. Ryazantseva; V. V. Novitsky; V. A. Bychkov; O. Ye. Chechina (Бюллетень сибирской медицины)
In the investigation it has been estimated the functional importance of gene interleukin 6 (IL6) polymorphism in progressing the chronic hepatitis C virus (HCV) infection. It has been determined the analysis of polymorphism –174 C/G frequency in gene IL6 promote zone at healthy donors and patients with chronic HCV-infection who are the Caucasian representatives of Tomsk region. The genotype GG carriers definitely dominated at patients with high activity rate of inflammatory process: it shows that G allele carriership have an impact on aggravation of inflammatory process activity in the liver patients with HCV-infections. In contrast to, carriership of C/G and C/C genotypes of polymorphism –174 C/G of gene IL6 have met more often at patients with minimal and moderate degree of inflammatory process.